Increasing the Production of Chili Peppers (Capsicum frutescens) with Application of Mycorrhiza Glomus Moseae and Gigaspora on Sea Sand Media - Mizan Maulana; Suswati; Zulheri Noer (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Utilizing coastal areas for agricultural purposes has not yet been widely adopted. The saline conditions and sandy soils typical of coastal regions make it difficult for plants to thrive. Chili peppers are a horticultural commodity with high economic value and are widely cultivated by farmers across various regions of Indonesia. Geographically and ecologically, Indonesia's coastal areas hold significant potential for agricultural development, fisheries, tourism, marine energy, and biodiversity conservation. Approximately 22% of Indonesia's total land area is coastal, making these regions highly strategic for local resource-based economic development. The total coastal area is estimated at over 327,000 km². Besides household use, cayenne pepper also serves as a raw material in the food and beverage industry. However, saline stress conditions can be toxic to plants. Salinity stress disrupts many aspects of plant physiology, including a decreased photosynthesis rate, cell damage due to sodium ion (Na⁺) accumulation, and reduced crop quality. This study employed a 4 × 3 randomized block factorial design (RBD) with three replications, yielding 12 treatment combinations across two treatment factors. The results showed that mycorrhizal application significantly affected plant height at 15, 30, and 45 days after sowing (DAS), as well as fresh weight at 110 DAS, but had no significant effect on other parameters. Among all observations, the Glomus mosseae mycorrhizal type consistently outperformed other mycorrhizal types in enhancing cayenne pepper growth. This study recommends further research on the use of organic materials as planting models suitable for coastal areas. Reason: The text was revised to improve clarity, coherence, and technical accuracy. Redundant phrases were removed, and terminology was standardized (e.g., “days after sowing" instead of "HST”). Sentence structure was enhanced for readability, and scientific names were corrected for proper formatting. Additionally, the flow of ideas was improved to connect better the background, methodology, results, and recommendations.